2016
DOI: 10.1101/052480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Driven Jamming in Growing Microbial Populations

Abstract: In natural settings, microbes tend to grow in dense populations [1][2][3][4] where they need to push against their surroundings to accommodate space for new cells. The associated contact forces play a critical role in a variety of population-level processes, including biofilm formation [5][6][7], the colonization of porous media [8,9], and the invasion of biological tissues [10][11][12]. Although mechanical forces have been characterized at the single cell level [13][14][15][16], it remains elusive how collect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Decreasing volume fraction may decrease the number of contacts between cells, reducing the amount of internal stress, as previously observed in collections of grains 18 and unicellular yeast 17 . Thus, by reducing the number of cell-cell interactions in week-8 clusters, decreasing volume fraction may also reduce the rate of internal stress accumulation.…”
Section: Nature Physicssupporting
confidence: 60%
See 1 more Smart Citation
“…Decreasing volume fraction may decrease the number of contacts between cells, reducing the amount of internal stress, as previously observed in collections of grains 18 and unicellular yeast 17 . Thus, by reducing the number of cell-cell interactions in week-8 clusters, decreasing volume fraction may also reduce the rate of internal stress accumulation.…”
Section: Nature Physicssupporting
confidence: 60%
“…Finally, we measured the compressive modulus of clusters of both genotypes. Previous studies demonstrated that the elastic modulus of individual yeast cells is relatively constant with respect to cell size 16 ; if individual snowflake yeast cells behave similarly, the compressive modulus may be expected to increase if interior volume fraction increases 17,18 . It is important to note that the distribution of cells within clusters is very heterogeneous 7,19 ; cells in the cluster interior are much more crowded than those at the periphery (Fig.…”
Section: Nature Physicsmentioning
confidence: 99%
“…The idea of phase transition has recently been proposed to explain the collective motility of many-cell systems such that increasing cell density would lead to glass transition that globally jams the systems' motion (41)(42)(43)(44). Our results may suggest a similar "disorder-to-order" transition in collective cell oscillations such that some critical cell population is required to ensure spatiotemporally organized, aligned, and polarized cell oscillations in the amnioserosa tissue.…”
Section: Resultssupporting
confidence: 51%
“…Agent-based models, therefore, need to be able to model the force exerted by growing cells, as well as the mechanical interactions induced by cell-cell contacts or contact with environmental boundaries. Further, it has been shown that the environment of an individual cell can influence its growth, which in turn influences the collective’s behavior through mechanical communication [8, 10, 14, 27, 34]. In particular, mechanical confinement can cause cells within the collective to grow at different rates [8, 10].…”
Section: Introductionmentioning
confidence: 99%